Poliomyelitis: The cause for the drop in vaccination coverage in Brazil (Research, Society and Development, 2023)
Introduction: Since 1994, Brazil has maintained a commitment to prevent the reintroduction of the polio virus within its territory, with a vaccination target of 95% of the population. However, since 2016, this target has not been met, leading to a concerning decline in vaccination coverage. This can be attributed to the COVID-19 pandemic, the anti-vaccine movement, and the implementation of austerity policies in healthcare and education. Aims: To identify the causes of the decline in polio vaccination coverage as presented in scientific studies. Methods: This is a narrative literature review conducted through the Lilacs, Scielo, PubMed, and BVS databases. Articles meeting the inclusion criteria were selected: studies conducted between 2018 and 2023, in English and Portuguese, complete, and available for consultation. Documents that did not meet the established criteria were excluded. Results e Conclusion: The decline in polio vaccination coverage is a result of various factors, including vaccine hesitancy, the anti-vaccine movement, and challenges related to the Brazilian Unified Health System (SUS) during the COVID-19 pandemic. Investment in the SUS is crucial to ensure adequate resources, professional training, and the improvement of vaccination facilities. Health communication strategies are essential to promote trust in vaccines and counter vaccine hesitancy and anti-vaccine movements. The research had limitations due to the scarcity of publications on the subject, suggesting the need for future research involving policymakers, professionals, and the population for a more comprehensive understanding of this phenomenon.